The Urgency of Developing a Teaching Factory for Increasing Financial Independence in Vocational Schools - Ratum; Babang Robandi; Rusdiono Muryanto (Nexus Publishing NXP, 2024)
This article discusses the urgency of developing teaching factories as a strategy to enhance financial independence in Vocational High Schools (SMK). SMK plays a crucial role in producing ready-to-work workforce, yet often faces financial constraints in managing its operations. The teaching factory method offers an innovative solution by integrating practical learning in schools with real-world work experience and financial income. This research employs a qualitative approach with interviews and observation techniques to gather data from several vocational schools that have implemented teaching factories. The re-search findings indicate that teaching factories effectively enhance the financial independence of SMKs through improved learning quality, increased competitiveness of graduates in the job market, and increased revenue through collaboration with industries. In conclusion, the development of teaching factories needs to be integrated into the management strategy of SMKs to enhance financial independence and educational quality.